FAKTOR –FAKTOR SOSIAL EKONOMI DAN PSIKOLOGIS YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI ANGGOTA KOPERASI CITRA BARU SEKTOR AGRIBISNIS - Badrudin, Redy; Nusril, .; Aminah, . (Jurnal AGRISEP, 2007)
The purpose of this research were to know description socio economic and pshicology factors, Participation rate and the related socio economic and pshicology factors and participated members Citra Baru Cooperative in agribusiness sector. This Researh use description and  analysis methode use Statistic non parametric Rank Spearman correlation , and interval  in 95 % significant. The factors is age, formal education, experience, family members, revenue of house hold, motivation credit and perception to the service, n agribusiness prorame. The research show in  Dec 13 th – Jan 13 th  in riak siabun village sukaraja Seluma. Participation rate in middle category, the Factors that related are formal education experience, motivation, and perception to the service Keywords : Socio economis and pshicolgy factors, cooperative, participation.